2021
DOI: 10.30773/pi.2020.0372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Outbreak on Children’s Mental Health: A Comparative Study with Children Diagnosed and Isolated from Their Parents

Abstract: Objective The COVID-19 outbreak has negatively affected children in many ways. This study aimed to compare the psychological responses of children exposed to different levels of stress during the COVID-19 outbreak.Methods The anxiety levels, negative thoughts, and quality of life of COVID-19-positive children with COVID-19-positive parents (Child+ group, n=17), COVID-19-negative children who are separated from COVID-19-positive parents (Parent+ group, n=59), and a control group (n=64) were compared. The partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…These results show that children's high anxiety levels are associated with separation from parents rather than COVID-19 positivity. 23 In our study, groups had similar internalizing symptoms' levels. This result may be related to not being separated from their parents in both groups.…”
Section: Discussionsupporting
confidence: 56%
“…These results show that children's high anxiety levels are associated with separation from parents rather than COVID-19 positivity. 23 In our study, groups had similar internalizing symptoms' levels. This result may be related to not being separated from their parents in both groups.…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, for the few children infected with COVID-19, most are infected because their parents are infected, they may be isolated with their parents. Only when the parents are infected and the child is not, the child is separated from the parents because the parents are isolated ( Kılınçel et al 2021 ). The separation of children from their parents due to isolation is an important factor that affects children psychologically.…”
Section: Mechanisms or Factorsmentioning
confidence: 99%
“…The separation of children from their parents due to isolation is an important factor that affects children psychologically. Research has concluded that children require the closeness of other people to feel safe, especially during stressful events, and children who are separated from their parents experience increased anxiety, which negatively affects their quality of life ( Kılınçel et al 2021 ). A cross-sectional study in Qatar found that in 149 COVID-19-infected children, the rate of separation anxiety (57.9%) was significantly higher than the normal prevalence ( Khan et al 2021 ; Shear et al 2006 ).…”
Section: Mechanisms or Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have explored the impact of the COVID-19 pandemic on children's daily lives or psychological health [14,15]. Children have experienced significant disruptions to their daily routines, with daycare and school closures in many countries.…”
Section: Introductionmentioning
confidence: 99%